Money, credit and imperfect competition among banks - Allen Head; Timothy Kam; Sam Ng; Isaac Pan (Queen's University, Department of Economics, 2022)
Using micro-level data for the U.S., we provide new evidence-at national and state levels - of a positive (negative) relationship between the standard deviation (coefficient of variation) and the average in bank lending-rate markups. In a quantitative theory consistent with these empirical observations, banks' lending market power is determined in equilibrium and is a novel channel of monetary policy. At low inflation, banks tend to extract higher markups from existing loan customers rather than competing for additional loans. As a result, banking activity need not be welfare-improving if inflation is sufficiently low. This result speaks to concerns regarding market power in the banking sectors of low-inflation countries. Normatively, under a given inflation target, welfare gains arise if a central bank can use additional liquidity-provision (or tax-and-transfer) instruments to offset banks' market-power incentives.
Keywords: E41; E44; E51; E63; G21; 330; Banking and Credit; Markups Dispersion; Market Power; Stabilization Policy; Liquidity